Abbas Amanat y Farzin Vejdani (eds.), Iran Facing Others: Identity Boundaries in a Historical Perspective, Nueva York, Palgrave Macmillan, 2012, 292 pp. - Hernández Berea, Agustín (Estudios de Asia y África, 2015)
Abbas Amanat y Farzin Vejdani (eds.), Iran Facing Others: Identity Boundaries in a Historical Perspective, Nueva York, Palgrave Macmillan, 2012, 292 pp.